Pengembangan E-LKPD Berbasis Inkuiri Berbantuan Articulate Storyline Tema 6 Subtema 1 Pembelajaran 1 Kelas IV SD Negeri 018092 Lobu Rappa T.A 2022/2023 - Simbolon, Mariana Olandri; Ananda, Lala Jelita; Simbolon, Naeklan; Siregar, Arifin; Parangin-Angin, Laurensia M. (Universitas Labuhanbatu, 2023)
The background of this research is the unavailability of E-LKPD which is able to attract students' interest in learning in grade IV SD. This study aims to produce Inquiry-based E-LKPD assisted with articulate storytelling that is valid, practical and effective in supporting learning success. This research is research and development using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subject of this research was class IV students at SDN 018092 Lobu Rappa and the object of this research was an inquiry-based E-LKPD with the aid of an articulate storyline. The results showed that the validation by stage I material experts before revision obtained a percentage of 68% in the category